2011
DOI: 10.1590/s1807-55092011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Associação de comorbidades e hábitos não saudáveis com a capacidade de caminhada em pacientes com claudicação intermitente

Abstract: Indivíduos com claudicação intermitente (CI) comumente apresentam comorbidades associadas e hábitos não saudáveis, como o tabagismo e a inatividade física. Todavia, o quanto esses fatores contribuem para a intolerância à caminhada desses indivíduos permanece incerto. Assim, o objetivo deste estudo foi analisar a associação das comorbidades e hábitos não saudáveis com a capacidade de caminhada de indivíduos com CI. A amostra foi composta por 66 indivíduos com CI de ambos os gêneros. Todos os indivíduos realizar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Both, symptomatic (IC) and asymptomatic OPAD are related with increased morbidity, mortality and a lower quality of life (1,2) . In Brazil, its prevalence is 10.5% in the population over 18 years of age, and 21.6% in individuals over 60 years old (3) . It characteristically affects the lower limbs and manifests as calf pain that is triggered by exercise and relieved by rest (1) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both, symptomatic (IC) and asymptomatic OPAD are related with increased morbidity, mortality and a lower quality of life (1,2) . In Brazil, its prevalence is 10.5% in the population over 18 years of age, and 21.6% in individuals over 60 years old (3) . It characteristically affects the lower limbs and manifests as calf pain that is triggered by exercise and relieved by rest (1) .…”
Section: Introductionmentioning
confidence: 99%
“…It characteristically affects the lower limbs and manifests as calf pain that is triggered by exercise and relieved by rest (1) . Several studies have shown that the functional capacity of patients with IC is reduced (3)(4)(5) . This evaluation can be performed by determining the walking ability and/ or physical activity level.…”
Section: Introductionmentioning
confidence: 99%